Pengaruh Metode Probing Prompting Setting Kooperatif dalam Pembelajaran Matematika terhadap Hasil Belajar Siswa - Muhammad Shiddiqien Kuddus; Ruslan; Awi (Issues in Mathematics Education (IMED), 2017)
This study is a quasi-experimental research that aims to identify: (1) student learning outcomes before and after applied cooperative Probing Prompting method in the experimental class; (2) student learning outcomes before and after applied cooperative learning model in the control class; (3) Probing Prompting method affected to student learning outcomes based on the increase of student learning outcomes from both classes; (4) the increase of mathematics learning outcomes of the students taught using Probing Prompting method. The population of this study is all students in grade X MIPA on six classes. The writer chose two classes using simple random sampling. The data were collected by using observation and test. The method of analyzing data used descriptive and inferential statistical analysis. The result of descriptive statistical analysis is (1) the average of pretest and posttest results of the students taught using cooperative Probing Prompting method and cooperative learning model are: (i) 3.18 and 64.76; (ii) 3.42 and 52.35; (2) the increase of mathematics learning outcomes of the students taught using Probing Prompting method is 64.76 classified as moderate category. The result of inferential statistical analysis is the increase of mathematics learning outcomes of the students taught using cooperative Probing Prompting method is greater than cooperative learning model.